Downlink Trafﬁc Scheduling in Green Vehicular Roadside Infrastructure - Hammad, Abdulla A. (My University, 2014)
Vehicular Ad-hoc Networks (VANETs) will be an integral part of future Intelligent Trans- portation Systems (ITS). In highway settings where electrical power connections may not be available, road-side infrastructure will often be powered by renewable energy sources, such as solar power. For this reason, energy efficient designs are desirable.
This thesis considers the problem of energy efficient downlink scheduling for road- side infrastructure. In the ﬁrst part of the thesis, the constant bit rate (CBR) air interface case is investigated. Packet-based and timeslot-based scheduling models for the theoretical minimum energy bound are considered. Timeslot-based scheduling is then formulated as a Mixed Integer Linear Program (MILP). Following this, three energy efficient online scheduling algorithms with varying complexity are introduced. Results from a variety of experiments show that the proposed scheduling algorithms perform well when compared to the energy lower bounds.
In the second part of the thesis, the variable bit rate (VBR) air interface option is considered. Ofﬂine scheduling formulations are derived that provide lower bounds on the energy required to fufill vehicle requests. An integer linear program (ILP) is introduced which can be solved to ﬁnd optimal ofﬂine VBR schedules. Two ﬂow graph based models are then introduced. The ﬁrst uses Generalized Flow (GF) graphs and the second uses time expanded graphs (TEGs) to model the scheduling problem. Four online scheduling algorithms with varying energy efficiency, fairness and computational complexities are developed. The proposed algorithms’ performance is examined under different traffic scenarios and they are found to perform well compared to the lower bound.
This thesis proposes different scheduling algorithm to be implemented on the Roadside Units in ITS environment. Both variable and constant bit rate cases are considered.
Keywords: ITS; VANET; Vehicular; Green; Scheduling; RSU; Electrical and Electronics; Power and Energy; Systems and Communications; Electrical and Electronics